2017
DOI: 10.1002/anie.201706157
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Utilization of Nitroalkyne Equivalents in Batch and Continuous Flow

Abstract: We report a method for overcoming the low stability of nitroalkynes through the development of nitrated vinyl silyltriflate equivalents. Because of their instability, nitroalkynes have only rarely been utilized in synthesis. The reactivity of these silyltriflates, which are prepared in situ, is exemplified by dipolar cycloaddition reactions with nitrones to give highly substituted 4‐nitro‐4‐isoxazolines in high yields. This approach has proven general for several different alkyl and aryl substituted alkynes. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…183 In 2017, Morse and Jamison used nitronium triflate as a reagent using batch and flow chemistry techniques for the nitration of TMS-acetylenes 315 to provide nitrated silyl triflates 316 as stabilized nitroalkyne equivalents (Scheme 83). 184 Subsequent elimination/dipolar cycloaddition reactions of 316 with nitrones gave highly substituted 4-nitro-4-isoxazolines 317 in high yields.…”
Section: Organic Nitronium Saltsmentioning
confidence: 99%
“…183 In 2017, Morse and Jamison used nitronium triflate as a reagent using batch and flow chemistry techniques for the nitration of TMS-acetylenes 315 to provide nitrated silyl triflates 316 as stabilized nitroalkyne equivalents (Scheme 83). 184 Subsequent elimination/dipolar cycloaddition reactions of 316 with nitrones gave highly substituted 4-nitro-4-isoxazolines 317 in high yields.…”
Section: Organic Nitronium Saltsmentioning
confidence: 99%
“…The flow protocol is able to carry out the entire reaction sequence in a good yield and a short residence time, minimizing the accumulation of potentially hazardous reaction intermediates. The entire process (generation of nitronium triflate, formation of the vinyl silyltriflate intermediate and [3+2] cycloaddition) lasts 21 min and gives good yield (Scheme ) …”
Section: ‐Membered Ringsmentioning
confidence: 99%
“…Recently, the generation of silyl triflates 57A derived from trimethylsilyl alkynes 57 as equivalents of nitro alkynes was reported by Jamison and co-worker in batch and continuous flow (Scheme 21). [52] Nitro alkynes suffer from poor stability and the application in organic synthesis appeared to be illusive. Jamison's group reported that treatment of alkynes 57 with a solution of nitronium triflate in sulfolane leads to the in situ formation of nitro alkynes 57B, which smoothly undergo [3+2] cycloaddition with nitrones to form stable 4-nitro-4-isoxazolines (58).…”
Section: Scheme 20 Fluorination Of Diarylacetylenesmentioning
confidence: 99%